Public Perception of Broadcast Coverage of the Independent National Electoral Commission in the Conduct of the 2023 Gubernatorial Election in Adamawa State - Bawul, Sabarka; Kente, Josiah Sabo; Akase, T. M. (International Journal of Humanities, Education, and Social Sciences, 2025)
This study assesses public perception of broadcast media coverage of the Independent National Electoral Commission (INEC) during the 2023 gubernatorial election in Adamawa State, Nigeria. Employing a survey research design, data were collected through structured questionnaires administered to a sample size of 400 respondents, drawn from a population of 2,196,566. Perception theory served as the theoretical framework, offering insights into how the public interprets and evaluates media content. The findings reveal that 69% of respondents identified talk shows as the most prominent form of broadcast programming used in the coverage, followed by political music jingles. Additionally, the public perceived broadcast media to have employed mild and non-inciting frames and to have maintained objectivity in their reportage of INEC's conduct during the election. The study concludes that public perception of broadcast coverage was largely favorable, attributing this to the media’s professional and impartial approach, which in turn fostered public trust. It recommends that broadcast media continue to employ balanced and non-provocative frames when reporting on electoral matters. Furthermore, the government is urged to implement policies that ensure media security, particularly during the coverage of sensitive electoral processes, to sustain positive public engagement and trust.